Estimands for atopic dermatitis clinical trials: Expert opinion on the importance of intercurrent events. (25th February 2023) - Bissonnette, R.; Eichenfield, L. F.; Simpson, E.; Thaçi, D.; Kabashima, K.; Thyssen, J. P.; Guttman‐Yassky, E.; Nunes, F. P.; Gamalo, M.; Ahmad, F.; Kuligowski, M.; Sun, K.; et al.
Abstract: Despite the emergence of novel targeted treatments for atopic dermatitis (AD), there is a lack of guidelines on standardizing analysis of clinical trial data. To define and estimate meaningful treatment comparisons, several factors, including intercurrent events, must be taken into account. Intercurrent events are defined as events occurring after treatment initiation that affect either the interpretation or existence of the measurements associated with clinical questions of interest. Due to the relapsing, unpredictable nature of AD, intercurrent events frequently occur in AD trials, such as use of rescue therapy for intense itch and sleep deprivation. Despite the impact of intercurrent events in AD, they are often handled in an inconsistent manner across trials, which limits results interpretation. The estimand framework is increasingly used to estimate treatment effects while accounting for intercurrent events. This review explores how guidance from the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) on the use of estimands can be applied to support AD clinical trial design and analysis. We propose that estimands are used in AD trials and defined early during trial design. The use of estimands can provide clinicians with interventional trial results that are more reflective of clinical practice, help facilitate comparisons across clinical trials, and are more informative to enable improved treatment selection for patients.